UJI BEBERAPA KONSENTRASI EKSTRAK DAUN BINTARO (Cerbera manghas L.) SEBAGAI PESTISIDA NABATI UNTUK MENGENDALIKAN HAMA ULAT JENGKAL (Plusia sp.) PADA TREMBESI (Samanea saman (Jacq.)Merr.)Samanea saman tree species that have great ability to absorb carbon d - Arlita, Tuti; ', Juliati; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Samanea saman tree species that have great ability to absorb carbon dioxide from the air. Samanea samangrowthnot be separated from the problem of pests and diseases. Pests that attack Samanea samanand often result in losses that Plusia sp. Indonesia has a very diverse flora, contains quite a lot of kinds of plants which are sources of pesticides that can be used for pest control. The use ofCerbera manghasleaf extractas a botanical pesticide for controlling Plusia sp. of the Samanea saman is an alternative that can be used as an environmentally friendly pesticide.This research aimed to know the effect ofCerbera manghas leaf extract in controlling Plusia sp. and determine the exact concentration of the level of Plusia sp. mortality of the Samanea saman.This research uses a Completely Randomized Design Method, which consists of 5 treatments and 4 replicates with concentration levels of botanical pesticide. B0 = concentration Cerbera manghas leaf extract 0 g/l of water; B1 = 5 g/l of water; B2 = 10 g/l of water; B3 = 15 g/l of wate;B4 = 20 g/l of water. The results showed that the application of Cerbera manghas leaf extract at the concentration of 20 g/l of water is the best concentration in controlling Plusia sp. with results initial time of death fastest is 3.00 hours, the fastest time of turning off 50% (LT50) is 11.25 hours (11 hours 15 minutes) and total mortality amounted to 92.50%.Â Keywords:Samanea saman, Plusiasp., Cerbera manghas leaf, botanical pesticide